Analisis Hukum Predatory Pricing pada Penjualan Kendaraan Listrik di Bawah Nilai Jual Kendaraan Bermotor - Muhammad Raikhan Nur Rifqi; Kukuh Tejomurti (Indonesian Publication Center, 2026)
The automotive industry plays a strategic role in the national economy and reflects increasingly complex competition, particularly in the Battery Electric Vehicle (BEV) market characterized by competitive pricing strategies. One emerging phenomenon is the sale of BEVs at on-the-road (OTR) prices below the Motor Vehicle Sales Value (NJKB), which potentially indicates predatory pricing from a competition law perspective. This study aims to analyze such practices and assess whether they may be classified as predatory pricing under Law Number 5 of 1999, as well as to examine the corresponding preventive legal mechanisms. This research employs a normative legal method using a statutory approach and deductive analysis through legal syllogism based on primary and secondary legal materials. The findings show that BEV sales below NJKB cannot automatically be categorized as predatory pricing, as NJKB represents an administrative fiscal value rather than production cost. Price discrepancies serve only as preliminary indicators requiring further economic analysis. Therefore, NJKB may function as an early warning system in detecting potentially unfair pricing practices.